2023
DOI: 10.1186/s40478-023-01627-5
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic oligodendrocyte precursor cell-derived VEGFA is associated with blood–brain barrier impairment

Narek Manukjan,
Daria Majcher,
Peter Leenders
et al.

Abstract: Cerebral small vessel disease is characterised by decreased cerebral blood flow and blood–brain barrier impairments which play a key role in the development of white matter lesions. We hypothesised that cerebral hypoperfusion causes local hypoxia, affecting oligodendrocyte precursor cell—endothelial cell signalling leading to blood–brain barrier dysfunction as an early mechanism for the development of white matter lesions. Bilateral carotid artery stenosis was used as a mouse model for cerebral hypoperfusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…VEGFA can be tested in plentiful tissues in vivo under physiological conditions ( Braile et al, 2020 ; Bujaldon et al, 2019 ). Besides, VEGFA expression can be regulated by multiple factors, with hypoxia being the most crucial regulatory factor ( Manukjan et al, 2023 ). Several studies also demonstrated that VEGFA can participate in multiple pathophysiological processes, such as atherosclerosis, collateral circulation formation, increased vascular permeability, brain edema, neuroprotection, and nerve regeneration in ischemic cerebrovascular disease ( Manukjan et al, 2023 ; Neill et al, 2020 ; Parab et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…VEGFA can be tested in plentiful tissues in vivo under physiological conditions ( Braile et al, 2020 ; Bujaldon et al, 2019 ). Besides, VEGFA expression can be regulated by multiple factors, with hypoxia being the most crucial regulatory factor ( Manukjan et al, 2023 ). Several studies also demonstrated that VEGFA can participate in multiple pathophysiological processes, such as atherosclerosis, collateral circulation formation, increased vascular permeability, brain edema, neuroprotection, and nerve regeneration in ischemic cerebrovascular disease ( Manukjan et al, 2023 ; Neill et al, 2020 ; Parab et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taking our ndings together, we propose the following: that reduced microcirculatory ow resulting from parasite sequestration in the brain 46,47 results suboptimal brain perfusion [48][49][50] and neuronal hypofunction (evidenced by falling neuronal transcript levels), which is associated with progressive increase in glial cell activity 43 (evidenced by a progressive increase in glial transcripts), and other vascular-(VEGFA-VEGFR2 signalling [51][52][53][54][55][56][57] , platelet activation and coagulation 58 ), and neuronal-(neurotrophin signalling 59 , long-term potentiation 60 and glutamatergic signaling 61,62 ) related adaptive processes during late-stages of cerebral malaria, which may turn maladaptive and pathological 60,63 .…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, success of clemastine as a remyelination therapy has been noted in clinical trials of relapsing multiple sclerosis with chronic demyelinating optic neuropathy [22]. In HI, oligodendrocytes are particularly vulnerable to hypoxia and hypoglycemia [49]. Evidence suggests that in attempts to rescue demyelinated areas following a stroke, there is an increase in the density of perivascular oligodendrocyte progenitor cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…In HI, oligodendrocytes are particularly vulnerable to hypoxia and hypoglycemia [49]. Evidence suggests that in attempts to rescue demyelinated areas following a stroke, there is an increase in the density of perivascular oligodendrocyte progenitor cells [49]. In term infants in particular, myelinated fibers are more metabolically active and hence more vulnerable to HI [50].…”
Section: Discussionmentioning
confidence: 99%